STEM-Based Information Literacy Design to Prepare Learners in the Face of the Industrial Revolution 4.0: Literature Review - Syarofa, Najwa (International Conference on Elementary Education, 2022)
The world has now changed amid the development of technology and began to enter the era of industrial revolution 4.0, where information becomes the primary need and the effectiveness of time is taken into account. Thus, preparing learners to be able to compete globally, and master the development of technology is an essential thing for the life of society and the progress of a country. This article discusses STEM-based information literacy design to prepare learners in the face of the industrial revolution 4.0. The study included a) literation of information, b) research skills, c) free learning of life, d) STEM integrated learning, e) learners' skills, f) the era of the industrial revolution 4.0.